Pneumatosis Cystoides Intestinalis: A Rare Benign Cause of Pneumoperitoneum. (31st July 2013) - Devgun, Puneet; Hassan, Hal
Abstract : Pneumatosis cystoides intestinalis is a rare gastrointestinal complication in the course of connective tissue diseases, especially in scleroderma, that can lead to pneumoperitoneum or obstruction. Findings on plain radiography may reveal radiolucent linear or bubbly circular air bubbles in the bowel wall, with or without free gas accumulation in the peritoneal cavity. Treatment of pneumatosis cystoides intestinalis ranges from supportive care to laparotomy.